The Verb "Ja’ala" in the Holy Quran: A Semiotic Study of Selected Examples from the Verses of the Holy Quran - Al-Maliki, Sami Hamed (Journal of Arabic Language Sciences and Literature, 2024)
The study aimed to examine the word "ja’ala" in the Holy Quran by understanding its meanings, comparing them with those in Arabic literature, and observing the Quran’s use of lexical meanings of the word under study. This was achieved by reviewing linguistic dictionaries regarding the meanings of the word, and following an inductive approach based on what is mentioned in linguistic dictionaries and Quranic exegesis. The study also analyzed selected texts containing the word "ja’ala" and its derivatives to reach conclusions. The study found that one of the most important tools for semantic analysis is paying attention to the context in which the word appears, whether in the Quran or elsewhere, in order to arrive at the precise meaning of the word. It also highlighted the applicability of modern semantic analysis in studying the words and vocabulary of the Quran to understand their meanings within the context in which they appear. Furthermore, it identified one of the key meanings of the word "ja’ala" as belief, particularly in the context of erroneous beliefs held by disbelievers. The study emphasized the significant role of context in clarifying the meaning of any word and giving it new meanings not found in linguistic dictionaries, but acquired through the context in which they appear. This includes the acquisition of new meanings for the verb "ja’ala" beyond those found in Arabic literature, such as taking on the meanings of (imposing) and (associating).